PENGEMBANGAN MODUL FISIKA INTERAKTIF BERBASIS HOTS (HIGH ORDER THINKING SKILL) UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA SMA PADA POKOK BAHASAN SUHU DAN KALOR - Rizqi Wahyu Irma Wati; Albertus Djoko Lesmono; Sri Handono Budi Prastowo (FKIP Universitas Jember, 2019)
Abstract This development research aims to produce physics interactive learning materials in heat and thermo topic, insightful HOTS (High Order Thinking Skill) that can enhance the literacy science ability of students. The background of this research is the low literacy science ability of senior high school students/MA. The research design used was Nieveen’s research design which consisted of three stages, namely preliminary research, prototyping stage, and assessement stage. The instruments used in this research were validation sheet and literacy science test. The results of expert validation retrieved that physics interactive learning materials insightful HOTS valid constructs and valid content. Based on development test results of the data analysis concluded: (1) the validity of physics interactive learning materials, insightful HOTS was at valid category with an average score of valid constructs was 4.17 and average score of valid content was 4, (2) the effectiveness of physics interactive learning materials in heat and thermo topic, insightful HOTS to improve students’ literacy science skill showed that the average of N-Gain score was 0.59 which was in the medium category, so the physics interactive learning materials in heat and thermo topic, insightful HOTS was effective in improving literacy science skill. Key Words: development, interactive learning materials, HOTS (High Order Thinking Skill), literacy science